Effects of static stretching, pnf stretching, and dynamic warm-up on maximum power output and fatigue - Aman, J.; Christensen, B. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The purpose of this study was to determine the effects of static stretching, PNF stretching, and dynamic warm-up on maximum power output and fatigue. Ten participants were recruited to perform a vertical jump test at 3 minutes and 20 minutes post-treatment for all treatments until voluntary fatigue. Participants performed a standard protocol including one of the stretching/warm-up treatments followed by two repeated, counter-movement, vertical jump tests. Results of the study showed no statistically significant differences in maximum power output although the dynamic warm-up group resulted in a 10% and 9% higher average output compared to the control group. Results also showed no statistically significant differences in percent decline in power output as well as time to voluntary fatigue, although there was up to a 6 s difference between treatments and the control group. Although this study concluded with no statistical significance, an argument could be made for applicable significance.